The characteristics of the Islamic garden: Lessons for an Islamic garden concept in Malaysia - Harun, Nor Zalina; Mansor, Mazlina; Zen, Ismawi; Md Jani, Haza Hanurhaza (American Scientific Publishers, 2017)
A garden is an outdoor space designed for the purpose of relaxation and recreation. Meanwhile, an Islamic garden is known as a garden that arise during the peak of Muslim civilisation. The main purpose of this garden is to solely remember the oneness of God as He is the creator of the universe. However, throughout the centuries, the values of the Islamic garden has started to be overlooked. This is due to the recent movement as a modern and contemporary garden design are started to be embedded into a garden design. Thus, this has led to the decreasing number of an Islamic garden design being adapted into a garden design. Hence, to bring back the values of the Islamic garden, this research is conducted as to investigate the physical characteristics of the Islamic garden, in order to discover the appropriate elements to be adapted in a garden design, especially in Malaysia. Two objectives are outlined for this research, which are to identify the physical characteristic of the Islamic garden based on three prominent gardens, the Persian garden, Andalusian garden and Mughal garden. The second objective is to evaluate the relevance of adopting the Islamic garden concept for a garden design in Malaysia. Two types of methods are employed in this research, namely the document analysis and site studies that are conducted at three gardens in Andalusia, Spain. The finding of this research covers on the reviews of the Islamic garden, the identification of the physical characteristic of the Islamic garden and finally, the relevance of adopting the Islamic garden concept in Malaysia. This study highlights the importance to understand and strengthen the knowledge on the values of the Islamic garden as it is the key to protecting and continuing the legacy of the Muslim civilisation. Keywords: Garden; Islamic garden; garden design; physical characteristics.